Spanish demystified - Petrow, Jenny (New York : McGraw-Hill, 2007)
Covers basic Spanish language skills such as pronunciation, common expressions, grammar and vocabulary, and includes exercises, chapter-ending quizzes, and a final exam.
Includes index.
Keywords: Spanish language -- Textbooks for foreign speakers -- English; Spanish as a second language; Spanish language -- Programmed instruction